A revision of the Argentinean endemic genus Eucranium Brullé (Coleoptera: Scarabaeidae: Scarabaeinae) with description of one new species and new synonymies - Ocampo, Federico Carlos (2010)
The South American genus Eucranium Brullé has been revised and now includes six species: E. arachnoides Brullé, E. belenae Ocampo new species, E. cyclosoma Burmeister, E. dentifrons Guérin-Méneville, E. planicolle Burmeister, and E. simplicifrons Fairmaire. Eucranium pulvinatum Burmeister is a new junior synonym of Eucranium arachnoides Brullé, and Eucranium lepidum Burmeister is a new junior synonym of E. dentifrons Guérin-MéNeville. The following lectotypes and neotypes are designated: Eucranium pulvinatum Burmeister, lectotype; Eucranium planicolle Burmeister, lectotype; Psammotrupes dentifrons Guérin-Méneville, neotype; and Eucranium lepidum Burmeister, neotype. Description of the genus and new species, diagnosis and illustrations, and distribution maps are provided for all species. A key to the species of this genus is provided, and the biology and conservation status of the species are discussed.